2017
DOI: 10.1021/acs.jpclett.7b01019
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Binding Modes of a Multidomain Protein to Lipid-based Nanoparticles by Relaxation-based NMR

Abstract: The interactions of two model multidomain proteins—covalently linked diubiquitins, Ub2—with lipid-based nanoparticles have been quantitatively probed by the measurements of NMR lifetime line broadening, ΔR2. By combined analysis of ΔR2 profiles arising from interactions with liposomes of varying sizes, an approach recently developed for the characterization of interactions of monoubiquitin with liposomes, we determine how the parameters of exchange (liposome binding) and dynamics of each individual domain of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Recent studies demonstrated the possibility of obtaining high‐resolution detail of nano‐bio interfaces . It emerged that simple protein molecules could be adsorbed on NPs at specific binding sites, in analogy with the mode of recognition of natural protein partners.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated the possibility of obtaining high‐resolution detail of nano‐bio interfaces . It emerged that simple protein molecules could be adsorbed on NPs at specific binding sites, in analogy with the mode of recognition of natural protein partners.…”
Section: Discussionmentioning
confidence: 99%
“…Large particles such as nanoparticles present difficulties in solution-state NMR due to their slow molecular tumbling and resulting short T 2 relaxation times and broad peaks. However, several solution-state NMR studies have examined binding between peptides and nanoparticles in situ. Ligand-detected NMR techniques, which do not rely on being able to observe the large nanoparticle in solution, are especially promising in this field.…”
mentioning
confidence: 99%
“…If Ub was immobile on the surface of QDs, then the observed 15 N−Δ R 2 values would be uniform for all the residues . Hence, the observed small variation in 15 N−Δ R 2 ∼3 (excluding few residues showing considerably small 15 N−Δ R 2 ) can be attributed to a global motion of Ub on the surface of QDs rather than a local motion at the individual residue level.…”
Section: Resultsmentioning
confidence: 95%
“…They showed that Ub in the bound state undergoes internal rotation about an axis approximately perpendicular to the lipid surface while simultaneously wobbling in a cone centered about the internal rotation . They also derived a formalism on the K63-linked and K48-linked Ub 2 (diubiquitin) interaction with lipid NPs, thereby analyzing the three binding modes involved in Ub 2 : direct binding and tethered binding of a single domain and simultaneous binding of both domains . In another study, they probed the interaction between TiO 2 NPs and huntingtin peptides htt NT and htt NT Q 10 .…”
Section: Introductionmentioning
confidence: 99%